Space, Place and Poetry in English and German, 1960-1975 - Thomas, Nicola (Geocriticism and Spatial Literary Studies, 2018)
Space, Place and Poetry in English and German, 1960-1975 examines the work of Paul Celan, J. H. Prynne, Derek Mahon, Sarah Kirsch, Edwin Morgan and Ernst Jandl, bringing together postwar English- and German-language poetry and criticism on the theme of space, place and landscape. Nicola Thomas highlights hitherto underexplored connections between a wide range of poets working across the two language areas, demonstrating that space and place are vital critical categories for understanding poetry of this period. Thomas's analysis reveals weaknesses in existing critical taxonomies, arguing for the use of 'late modernist' as a category with cross-cultural relevance, and promotes methodological exchange between the Anglophone and German traditions of landscape, space and place oriented poetic criticism, to the benefit of both.